Organization Strategies for Progressed Alter in African Money related Educate - Cisse, Mohammed; Barry, Mouctar; Diallo, Mouctar (oneamrd (One a Mllions Dreams Corporation), 2024)
The computerized change of money related educate in Africa speaks to an opportunity for modernization and development, but it moreover comes with unused challenges and dangers. In this setting, chance administration techniques play a vital part in guaranteeing the victory and maintainability of these educate. Taking the Caisse Populaire d'Épargne et de Crédit de Guinée (CPECG) - Yètè Mali as an illustration, this article investigates the distinctive approaches received to distinguish, evaluate and moderate the dangers connected to advanced change. By executing strong security measures, guaranteeing viable information administration, and reinforcing checking and occurrence administration, budgetary teach can effectively explore the advancing computerized scene whereas securing the interface of their clients and of their organization